Measurement of MMP-7 in micro-volume peripheral blood: development of dried blood spot approach - Jiang, Jingying; Liu, Shuyang; Du, Min; Deng, Jiale; Chen, Gong; Yang, Yifan; Dong, Rui; Fang, Zhuo; Zheng, Shan (Frontiers in Pediatrics, 2023)
Serum matrix metalloproteinase-7 (MMP-7) is significant in differentiating biliary atresia (BA). This study aims to develop a new peripheral blood quantitative collection device to detect MMP-7 levels via dried blood spot (DBS).Methods: This is a diagnostic accuracy test. Serum and DBS MMP-7 concentrations were measured using an ELISA kit. Intraoperative cholangiography and subsequent histological examinations were used to confirm BA diagnoses.Results: A total of 241 infants with obstructive jaundice were enrolled, among whom 168 were BA.Linear regression showed DBS MMP-7 correlated well with serum MMP-7 (R= 0.93, P < 0.001). The best cut-off value of serum MMP-7 for BA was 25.9 ng/ml, achieving the area under the ROC curve (AUC) of 0.962 (95% CI: 0.941, 0.983), and the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were 86.9%, 94.5%, 97.3% and 75.8%, respectively. The best cutoff value of DBS MMP-7 for BA was 12.5ng/ml, achieving the AUC of 0.922 (95% CI: 0.888, 0.956), and the sensitivity, specificity, PPV, and NPV were 86.9%, 89.0%, 94.8%, and 74.7%, respectively. The dried blood spots were intervened under different storage conditions, including 1-5 days at room temperature, 2 or 3 days at 30℃ and 2 or 3 days at 37℃. The DBS MMP-7 concentration under different storage conditions had good correlation and consistency with that at -80℃.Conclusions: Serum and DBS MMP-7 correlate well, both of which have high accuracy in the diagnosis of BA, while the requirements for the storage of DBS are low.